2023
DOI: 10.1080/19317611.2023.2212651
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Safety or Pleasure Determine Condom Use Intentions Differently Depending on Condom Availability and STI Risk

Abstract: Running head: Regulatory Focus and Condom Use Acknowledgments This work was funded by the Social Observatory of the "la Caixa" Foundation (Ref.: LCF/PR/SR20/52550001) and by a grant awarded by Fundação para a Ciência e a Tecnologia (Ref.: 2020.00523.CEECIND) awarded to DLR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Specifically, participants who were predominantly focused on promotion (vs. prevention) reported having condomless sex more often (H1) and with a larger number of casual partners (H2; particularly in vaginal and oral sex), more sexual satisfaction with themselves and with their partners (H3), and more positive (and less negative) affect when thinking about their condomless sex experiences (H4). This pattern of results remained the same after controlling for country of residence, converging with findings from other cultural contexts (see also Evans-Paulson et al, 2022;Rodrigues, 2022Rodrigues, , 2023. The results of our study extend past research by showing that safety and pleasure motives have distinct implications for the sexual practices and the sexual experiences people have with their casual partners.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, participants who were predominantly focused on promotion (vs. prevention) reported having condomless sex more often (H1) and with a larger number of casual partners (H2; particularly in vaginal and oral sex), more sexual satisfaction with themselves and with their partners (H3), and more positive (and less negative) affect when thinking about their condomless sex experiences (H4). This pattern of results remained the same after controlling for country of residence, converging with findings from other cultural contexts (see also Evans-Paulson et al, 2022;Rodrigues, 2022Rodrigues, , 2023. The results of our study extend past research by showing that safety and pleasure motives have distinct implications for the sexual practices and the sexual experiences people have with their casual partners.…”
Section: Discussionsupporting
confidence: 89%
“…Past research has examined prevention and promotion scores separately (e.g., , computed a continuous index (e.g., Evans-Paulson et al, 2022;Rodrigues et al, 2019), or categorized participants according to their predominant focus (e.g., Rodrigues, 2023). We took a different approach and sought to identify for the first time whether different latent profiles emerged based on the responses to our main predictor measure (i.e., regulatory focus in sexuality).…”
Section: Current Study and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aligning with this reasoning, recent research has shown that people who are more focused on prevention in sexuality tend to be more lenient with their condom use intentions with casual partners, but only when contextual cues indicate lower health risks (Rodrigues, 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Sexual pleasure during sex is well established to lead to higher sexual satisfaction and may also be associated with improved quality of life [ 25 , 26 ]. However, others have suggested that focusing only on having sex for pleasure might lead to individuals deprioritising or neglecting other aspects of sexual health, perhaps leading to things like reduced condom use [ 27 ] which could lead to decreased well-being for some. As such, the association between pleasure as a sexual motivation and physical QoL needs further exploration.…”
Section: Introductionmentioning
confidence: 99%